HUBUNGAN MOTIVASI DENGAN PERILAKU PETANI PENANGKAR BENIH PADI BERSERTIFIKAT DALAM PENGGUNAAN APLIKASI BIDANG PERTANIAN BERBASIS ANDROID DI KECAMATAN PEMAYUNG KABUPATEN BATANGHARI - Rendra, Rendra; Jamaluddin, Jamaluddin; Sardi, Idris; Sativa, Fendria (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
This research aimed to know (1) the motivation of certified rice seed breeders in the application of android-based agriculture in Pemayung District, Batang Hari Regency (2) the behavior of certified rice seed breeders in the use of android-based agricultural applications in Pemayung District, Batang Hari Regency ( 3) the relationship of motivation with the behavior of farmers in the use of applications based on android agriculture with the application of certified rice seed breeding techniques in Pemayung Sub-District, Batang Hari Regency. The analysis used in this research was a non-parametric analysis method through Chi-Square test by x2 test, Chit, r test, and thit test with 2x2 contingency table at an error rate of 5%. This research was conducted in July-August 2019. The results of the analysis obtained x2hit = 9,52> x2 tab = 3,84, meaning that there is a real relationship between the motivation of farmers with the behavior of certified rice seed breeders in the use of android-based applications in Pemayung District, Batang Hari Regency. The value of thit = 4.69> ttab = 1.67252, meaning that there is a significant relationship between the motivation of farmers with the behavior of certified rice seed breeders in the use of android-based applications in Pemayung District, Batang Hari Regency in real terms.